Assessment of meteorological and socioeconomic drought conditions in the Tekeze watershed, northern Ethiopia - Tela, Yonas Tesfay; Wassie, Simachew Bantigegn; Ferede, Mehrete Belay (Frontiers in Environmental Science, 2024)
In northern Ethiopia, meteorological droughts overwhelm crops and often lead people to food insecurity and poverty traps. Socioeconomic droughts similarly aggravate poverty and impact livelihoods; causing significant challenge on communities. Such issues in the area were not researched and not well addressed. Hence, the objective of this study was to evaluate the temporal and spatial trends of meteorological drought and the implied socioeconomic drought impacts in the Tekeze Watershed. The main data sources for this study included survey questionnaires, field observations, and CHIRPS data. Precipitation data from various stations were also employed to validate the CHIRPS data using a random forest regression model. The results revealed a strong coefficient of determination for the model, with values of 0.88, 0.87, 0.88, and 0.84 for the Mekele Obseva, Sekota, Yichila, and Ashere stations, respectively. This indicates that the precipitation recorded at these stations can be well-explained by the CHIRPS data. The temporal trends of meteorological drought showed that most of the years faced shortage of rainfall, where the year 2015 exceptionally faced a severe drought. The drought conditions in the area were exacerbating from time to time with a drought reoccurrence period of 2 years. The socioeconomic drought also found similar results within the agricultural drought that the years 2000, 2002, 2004–5, 2009–11, 2013–15, 2017, and 2021–23 were affected by droughts of different severity levels and associated socioeconomic impacts. Accordingly, almost all (99.5%) of the respondents reported that they were personally experiencing droughts. The major causes of drought in the study watershed were climate variability, land use changes, land degradation, water mismanagement, deforestation, war, and desert locusts. The consequences of these overlapping crises include pandemics, malnutrition, displacement, crop losses, desertification, and conflicts over resource use. While proposed interventions like improved irrigation, water infrastructure, drought-resistant crops, and emergency relief were intended to address these issues, ill-guided procedures and inadequate execution have undermined their effectiveness. Thus, these measures have not been successfully implemented and have fallen short of addressing the tangible impacts of drought. To this end, the study recommends effective implementation of the mitigation measures initially implemented by the government and nongovernmental organizations, emphasizing the active involvement of the local community.